Design for 4D printing: A voxel-based modeling and simulation of smart materials. (5th August 2019) - Sossou, Germain; Demoly, Frédéric; Belkebir, Hadrien; Qi, H. Jerry; Gomes, Samuel; Montavon, Ghislain
Abstract: In the wake of the breakthrough being by additive manufacturing (AM), there is another rapidly growing manufacturing progress: 4D printing (4DP). It is basically AM with, inter alia, smart materials (SMs). Owing to the stimulus-responsive behaviors of these materials, the parts so manufactured are imbued with the ability to change. 4DP is being given huge research efforts regarding its manufacturing aspects. However so little is made to let designers explore the so uncovered design space. Compared to DFAM, what could be called Design for 4D printing (DF4DP) does lag far behind. In this article, a modeling framework for simulating SMs and conventional materials behaviors on a voxel basis is proposed; this allows for arranging materials in any distribution and rapidly evaluating the behavior of the distribution. Homogeneous and heterogeneous objects made of conventional materials and SMs were modeled and simulated. The modeled SMs were limited to non-programmable shape changing SMs including: piezoelectric material, electro-/magneto-/photostrictive materials and hydrogel. A printed smart valve and a theoretical actuator (both from other publications) were used as test cases. These simulations have a speed reasonable for the design iterations needed in conceptual design phase and they yield results in good agreement with physics. Graphical abstract: Unlabelled Image Highlights: Conceptual design framework for 4D printing is proposed. Voxel based modeling and simulation of non-programmable shape changing smart materials Simulation of heterogeneous objects made of conventional materials and smart materials Fast evaluation of any material distribution behavior upon exposure to stimulus